Remote leadership in public sector: a systematic review and future research directions - Solichah, Sinta Fanidatus; Nadia, Fiona Niska Dinda (Universitas Negeri Surabaya, Indonesia, 2026)
The purpose of this article is to comprehensively review the existing research on remote leadership, especially in the public sector. This study highlights the main problems with previous research findings on remote leadership based on theoretical approaches, methods, antecedents and consequences on the effectiveness of public sector organizations. This study adopted a systematic literature review (SLR) approach based on Tranfield et al. (2003) and PRISMA guidelines by analysing 12 high-quality articles indexed in Scopus from 2016 to 2025. The findings focus on antecedents, mediators, moderators, and consequences of remote leadership, resulting in an integrative conceptual framework. The study reveals that remote leadership effectiveness is strongly influenced by digital competence, trust-building, and transformational leadership behaviours. Furthermore, this study identifies critical research gaps, particularly the limited focus on public sector organisations and non-Western contexts. In addition, the findings that remote leadership is a new leadership approach that uses few theoretical sources in defining the concept of remote leadership. The study contributes by offering a structured multi-level framework and proposing future research directions. Practical implications emphasize the need for digital leadership capability development and organizational readiness in virtual environments.